Support for Alcohol Policies in Marginalized Populations. (21st December 2020) - Trangenstein, Pamela J; Mulia, Nina; Lui, Camillia K; Karriker-Jaffe, Katherine J; Greenfield, Thomas K; Jones-Webb, Rhonda
Abstract: Aim: Kingdon [(2014 ) Agendas, Alternatives, and Public Policies. Essex. United Kingdom: Pearson Education Limited] argues that windows of opportunity to pass policies emerge when problems, solutions and policy support co-occur. This study aims to identify a set of alcohol policies with the potential to reduce alcohol-related disparities given high levels of support from marginalized groups, such as racial/ethnic minorities and lower-income groups. Methods: This study used data from five US National Alcohol Surveys, which were based on household probability samples of adults in 1995 ( n  = 4243), 2000 ( n  = 5736), 2005 ( n  = 1445), 2010 ( n  = 4164) and 2015 ( n  = 4041). We used multiple logistic regression to determine the odds of policy support by racial/ethnic group and income level, considering price, place and marketing policies as well as individual-level interventions. Results: Overall a majority of Americans supported banning alcohol sales in corner stores (59.4%), banning alcohol advertisements on television (55.5%), and establishing universal health coverage for alcohol treatment (80.0%). Support was particularly high among Blacks, Hispanics/Latinos and lower-income persons. Multivariate models showed that compared with White people, foreign-born Hispanics/Latinos had the most robust levels of support, including raising alcohol taxes ( aOR  = 2.40, 95% CI: 2.00, 2.88, P  < 0.0001), banning alcohol sales in corner stores ( aOR  = 2.85, 95% CI: 2.22, 3.65, P  < 0.0001) and reducing retail sales hours ( aOR  = 2.91, 95% CI: 2.38, 3.55, P  < 0.0001). Conclusion: Of the policies examined, banning alcohol sales at corner stores is most likely to be in a "window of opportunity" for reducing alcohol-related disparities. By simultaneously reducing population-level consumption and harms from others' drinking, place-based policies have the potential to reduce harms experienced by marginalized groups.